DAMPAK PERKAWINAN DI USIA DINI (STUDI KASUS DI DESA KEDAWANG KECAMATAN NGULING KABUPATEN PASURUAN) - Yusrolana yusrolana; Fathurrahman Alfa; Dwi Ari Kurniawati (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2019)
Marriage is something sacred is worth worshiping to God, following the sunnah of the Prophet and carried out on the basis of sincerity and with a sense of responsibility. In Chapter 1 Article 1 of the Law of the Republic of Indonesia Number 1 of 1974 explains that marriage is an inner and outer bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family based on the One Godhead. The purpose of marriage as explained in the Qur'an is Ar-Rum verse 21